2012
DOI: 10.15365/joce.1601062013
|View full text |Cite
|
Sign up to set email alerts
|

Educational Salvation: Integrating Critical Spirituality in Educational Leadership

Abstract: Improving education for students in K-12 urban settings remains a slow-paced and difficult task, with many successes in student learning being episodic at best. The disconnect between government mandates to improve schools and persistent societal issues of poverty and inequity act to increase stress on teachers and educational leaders working in urban schools. Drawing upon the strengths of the African-American community and its collective historical experiences, this study explores creative ways to integrate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In Indonesia, Islam is a core aspect of individual and national identity, but there is great variation within Islam – this means that the ways a principal engages with the socio-religious aspects of their practice can shape the way education is practiced in their school (Jackson and Parker, 2008; Raihani, 2017; Srimulyani, 2012; Tan, 2011). While it is beyond the scope of this study to determine whether or not this might be a direct effect, this study suggested that principals do have an indirect effect on socio-religious dynamics in their schools, much like the relationship between school culture and leadership (Hallinger, 2003; Louis and Wahlstrom, 2011; Lumby and Foskett, 2011; McCray et al ., 2012; Winkel and Ganiel, 2017). Based partly on their own conviction and partly on school and community norms, principals made decisions based on their interpretation of Islam that was manifest in the policies, practices and procedures in their school (Brooks and Brooks, 2018).…”
Section: Discussion: Principal Leadership As Socio-religious Curationmentioning
confidence: 87%
See 2 more Smart Citations
“…In Indonesia, Islam is a core aspect of individual and national identity, but there is great variation within Islam – this means that the ways a principal engages with the socio-religious aspects of their practice can shape the way education is practiced in their school (Jackson and Parker, 2008; Raihani, 2017; Srimulyani, 2012; Tan, 2011). While it is beyond the scope of this study to determine whether or not this might be a direct effect, this study suggested that principals do have an indirect effect on socio-religious dynamics in their schools, much like the relationship between school culture and leadership (Hallinger, 2003; Louis and Wahlstrom, 2011; Lumby and Foskett, 2011; McCray et al ., 2012; Winkel and Ganiel, 2017). Based partly on their own conviction and partly on school and community norms, principals made decisions based on their interpretation of Islam that was manifest in the policies, practices and procedures in their school (Brooks and Brooks, 2018).…”
Section: Discussion: Principal Leadership As Socio-religious Curationmentioning
confidence: 87%
“…Other principals intentionally selected teachers who were hafiz, whether or not their teaching strategies were engaging, appropriate or effective. As curators, Islamic principals were able to privilege their personal socio-religious beliefs over others, which informed and influenced the decisions they made, the pedagogical practices in the school, and the rules they enforced (Dantley, 2010; Marshall, 2014; McCray et al ., 2012). Those choices, collectively considered, pushed principals to foster school cultures that moved students and teachers along a continuum, either towards a more progressive or more conservative enactment of Islam.…”
Section: Discussion: Principal Leadership As Socio-religious Curationmentioning
confidence: 99%
See 1 more Smart Citation
“…Professionals in these occupational areas had an expressed interest in incorporating spirituality within professional practice. Additionally, earlier studies have used critical spirituality in educational settings to understand principals' roles in primary education settings (Dantley, 2010;McCray et al, 2012;Scanlan, 2011). However, this study supported the idea that leaders in any sector can use critical spirituality to advance their leadership capacity.…”
Section: Develop Critical Spirituality As a Leadership Frameworkmentioning
confidence: 51%
“…Embedded in the four elements of critical spirituality is the idea of tragicomic hope. According to McCray et al (2012), "While engaging in critical self-reflection, deconstructive interpretation, performative creativity, and transformative action, leaders must believe that tomorrow will be a better day than yesterday" (p. 100).…”
Section: The Main Elements Of Critical Spiritualitymentioning
confidence: 99%